Salivary Cortisol Profile Under Different Stressful Situations in Female College Students: Moderating Role of Anxiety and Sleep. Issue 5 (October 2018) - Suh, Minhee
Abstract : ABSTRACT: Objectives: This study investigated the level of cortisol under different stressful situations and its relationship with sleep and anxiety in female college students.Methods: Salivary cortisol was measured 6 times a day during a routine period free of examination stress and a stressful period. Area under the curve (AUC) was calculated for cortisol level for awakening response (AUCAG ) and during the day (AUCTG ). Sleep characteristics and anxiety were measured using an actigraph and the Spielberger State-Trait Anxiety Inventory, respectively, during the different periods.Results: Thirty-six people participated in the study. During the stressful period, anxiety had a positive correlation with sleep efficiency ( P = .020), wake after sleep onset ( P = .023), and mean wake episodes during sleep ( P = .048). Poorer sleep efficiency ( P = .014), greater wake after sleep onset ( P = .008), and mean wake episodes during sleep ( P = .044) were significantly associated with less AUCAG . Trait anxiety was significantly higher in participants with greater AUCTG ( P = .008).Conclusions: Female college students with increased anxiety under the stressful situation slept better. Those with poor sleep showed attenuated morning cortisol secretion. Those with higher trait anxiety had greater cortisol during the day. Abstract : Supplemental digital content is available in the text.